(3GdLGeY GdUMjMs - (3eMeO Hf ESeGYjd Hf EHQGgje GdLYaj GdHNGQj, CHh YHO Gddg , J (B256 (3g` s ((3MdH s)
(3ChdgG (B:s
(3jHOC HHGH QaY GdEeGe jOg ai GdESJSbGA s
(3BNQgG (B:s
(3hGUfY ai YeQJc ceG JUfY ai MLJc abdJ dYWGA CQGO GdEfbGA Mjf CeQg Cf jZSd KdGK eQGJ bGd fYe GdMeO ddg QH BNQ GdLRA GdKGdK ef CUd NeSI YTQ LRAkG ef UMjM GdHNGQi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B34 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B52s
Keywords: (3GdMOjK h GdeUWdMs